Истоки предания «Как Пушкин учился в школе». Замечания к московским легендам о Пушкине, записанным Евгением Барановым - КАЛАВСКИ, ЖОФИЯ (SlavVaria, 2021)
The sources of the legend “How Pushkin studied in school”. Reflections on the Pushkin legends noted down by Evgeny Baranov in Moscow. In my study I analyze the Pushkin legends noted down by Russian ethnographer Evgeny Baranov in the 1920s in Moscow. My research primarily focuses on the myth “How Pushkin studied in school”, although I also partly discuss what sources the peasant-born speakers could have used when forming their Pushkin image in the myths “Pushkin and the tsar”, “Pushkin and Gogol”, “How Pushkin was taken out by his wife”, and “Bruce, Sukharev, and Pushkin”. I demonstrate how the legend “Как Пушкин учился в школе” (“How Pushkin studied in school”) has a primary source in the materials surviving from the first year of the Tsarskoye Selo lyceum, variants of which became perennial pieces in the popular anecdote collections of the end of the nineteenth century. Beyond the philological investigation it is especially interesting to follow the metamorphosis during which the literary anecdote loses its generic characteristics and expands into a “biographic” story on a central protagonist. The analysis of the Baranov myths draws attention to the power of the Pushkin monument in Moscow to create meaning and the influence of other legendary Moscow characters on the reception of the Pushkin character.